Porosity and optical properties of zirconia films prepared by plasma ion assisted deposition - Franke, C.; Stenzel, O.; Wilbrandt, S.; Schroeder, S.; Coriand, L.; Felde, N.; Tuennermann, A. (Applied Optics, 2017)
The porosity of zirconia films prepared by plasma ion assisted deposition has been investigated by means of optical (spectrophotometric) and nonoptical analytic techniques such as transmission electron microscopy, xray reflection, and energy dispersive X-ray spectroscopy. A discrimination between large (open) and small (closed) pores was achieved by means of measurement of the thermal and vacuum-to-air shift. Depending on the level of plasma assistance during film preparation, the porosity was found to vary between 30 vol. % and nearly 0 vol. %. With decreasing porosity, the surface roughness determined by atomic force microscopy tends to decrease as well.
CRIS-Team Scopus Importer:2023-04-20